Nuclear magnetic resonance-based metabolomic analysis in the assessment of preclinical atherosclerosis in type 1 diabetes and preeclampsia. (January 2021) - Amor, Antonio J.; Vinagre, Irene; Valverde, Maite; Urquizu, Xavier; Meler, Eva; López, Eva; Alonso, Nuria; Pané, Adriana; Giménez, Marga; Codina, Laura; Conget, Ignacio; Barahona, Maria J.; et al.
Abstract: Aims: Evaluate the role of plasma metabolomics in atherosclerosis according to the presence of type 1 diabetes (T1D) or previous preeclampsia. Methods: We recruited 105 women without cardiovascular disease and last pregnancy ≥5 years previously, divided according to the presence of T1D or previous preeclampsia. Preclinical atherosclerosis was defined as the presence of carotid plaque (intima-media thickness ≥1.5 mm) assessed by ultrasonography. Metabolomics were evaluated by nuclear magnetic resonance (NMR). Bivariate and multivariate-adjusted differences in NMR-metabolomics were evaluated. Results: The participants were 44.9 ± 8.1 years-old; 20% harbored plaques. There were significant differences in lipidic-, energetic- and nitrogen-related metabolites according to the presence of T1D/preeclampsia (p < 0.05). In multivariate-adjusted models (by age, statins, blood pressure and T1D/preeclampsia), only lipidomic-related metabolites were associated with atherosclerosis in the whole sample. However, stronger associations were observed in women with previous preeclampsia (vs. without; per 0.5 mmol/L increments); phosphatidylcholine, OR 4.08 (1.32–27.22); free cholesterol, 5.18 (1.22–21.97); saturated fatty acids, OR 2.99 (1.37–6.48); w-7, OR 2.29 (1.15–4.56); and w-9 fatty acids, OR 1.49 (1.00–2.23). Conclusions: NMR-metabolomics showed a differential pattern according to the presence of T1D/preeclampsia in relation to preclinical atherosclerosis. Since most of these metabolites mirror lifestyle factors, they could help tailor dietetic advice in high-risk women.